2018
DOI: 10.1021/acs.jpca.8b08618
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Excitation of HD by Hydrogen Revisited

Abstract: The HD molecules are key species for the cooling of pristine gas at temperatures below 100 K. They are also known to be key tracers of H2 in protoplanetary disks and thus, they can be used as a measure of protoplanetary disks mass. Accurate modeling of the cooling mechanism and of HD abundance in astrophysical media requires a proper modeling for its excitation by both radiative and collisional processes. Here, we report quantum time-independent calculations of collisional rate coefficients for the rotational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…Therefore, it is crucial to investigate the chemical reactions involving HD, especially with neutral and ionised atoms, in order to characterise the cooling dynamics. If the reaction with the most abundant species H has been widely studied (see for instance (Flower & Roueff 1999;Ely et al 2016;Desrousseaux et al 2018)), very little is known about its ionic counterpart H + + HD, which is the subject of the present article.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to investigate the chemical reactions involving HD, especially with neutral and ionised atoms, in order to characterise the cooling dynamics. If the reaction with the most abundant species H has been widely studied (see for instance (Flower & Roueff 1999;Ely et al 2016;Desrousseaux et al 2018)), very little is known about its ionic counterpart H + + HD, which is the subject of the present article.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, since the Hamiltonian is symmetric with respect to interchange of the two hydrogens, there will be no coupling between odd (ortho) and even (para) rotational states of H 2 , so that the number of coupled channels is reduced. We then obtained inelastic, reactive and exchange integral cross sections following the approach described by Tao and Alexander 43 and recently used to study the rotational excitation of several hydrides in collision with H [44][45][46][47] . Excited vibrational states up to v = 17 and up to j = 6 (E max = 4.4 eV) are included in the basis to ensure convergence of the cross sections.…”
Section: Close Coupling (Cc) Calculationsmentioning
confidence: 99%
“…This was confirmed by subsequent theoretical studies which revealed that the angular distribution of the scattered HD in collisions with H 2 was dominated by a single (l = 2) partial-wave shape resonance as around 1 K 19 . Collisions of HD with H 2 are also of current astrophysical interest as the HD molecule is believed to have played an important role in the cooling of the primordial gas in the formation of the first stars and galaxies [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%